2022
DOI: 10.1021/acsami.1c21700
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic MOF Nanoparticles Delivery of C-Dot Nanozyme and CRISPR/Cas9 System for Site-Specific Treatment of Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) of unknown etiology affecting the colon and rectum. Previous studies have found that reactive oxygen species (ROS) overproduction and transmembrane glycoprotein CD98 (encoded by SLC3A2) upregulation played important roles in the initiation and progression of UC. On the basis of this, a biomimetic pH-responsive metal organic framework (MOF) carrier was constructed to deliver carbon nanodot-SOD nanozyme and clustered regularly interspaced shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…In the past decade, many strategies have been employed to scavenge excessive ROS and alleviate inflammation responses, among which emerging therapeutic approaches utilizing enzymatically active nanomaterials as antioxidants have attracted more and more attention ( Thakur et al, 2019 ; Shah et al, 2020 ; Wang L. et al, 2021 ). In recent years, many carbon-based nanomaterials with antioxidant activities have been developed to regulate abnormal ROS levels in organisms due to their efficient catalytic activities like enzymes ( Das et al, 2019 ; Dehvari et al, 2020 ; Wang H. et al, 2021 ; Li et al, 2021 ; Xue et al, 2021 ; Ma et al, 2022 ). Carbon dots (CDs) nanozyme, as a “new star” among nanozymes, have potential anti-inflammatory therapeutic applications owing to their high efficiency in promoting electron transfer for scavenging ROS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, many strategies have been employed to scavenge excessive ROS and alleviate inflammation responses, among which emerging therapeutic approaches utilizing enzymatically active nanomaterials as antioxidants have attracted more and more attention ( Thakur et al, 2019 ; Shah et al, 2020 ; Wang L. et al, 2021 ). In recent years, many carbon-based nanomaterials with antioxidant activities have been developed to regulate abnormal ROS levels in organisms due to their efficient catalytic activities like enzymes ( Das et al, 2019 ; Dehvari et al, 2020 ; Wang H. et al, 2021 ; Li et al, 2021 ; Xue et al, 2021 ; Ma et al, 2022 ). Carbon dots (CDs) nanozyme, as a “new star” among nanozymes, have potential anti-inflammatory therapeutic applications owing to their high efficiency in promoting electron transfer for scavenging ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al designed the tellurium-doped carbon quantum dots which can scavenge H 2 O 2 to protect cells under ambient condition ( Chen et al, 2020 ). Ma et al (2022) reported the CDs with excellent superoxide dismutase enzymatic activity, which could scavenge ROS effectively ( Ma et al, 2022 ). More recently, Wang et al presented a novel CDs which exhibit well free radical scavenging activity and have potential to be a new highly effective antioxidant relying on the phenol-like groups ( Wang X. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using positive and negative charges to target inflammatory sites, Ma et al used macrophage membrane to improve the targeting ability of their biomimetic system. 147 They designed C-dot nanozyme@CD98 CRISPR/Cas9 plasmid@ZIF-8@Macrophage membrane (CCZM) (Fig. 13(c)).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Scavenge ROS effectively 2. pH-responsive, immune escape, and inflammation targeting 3. Reduced the expression of proinflammatory cytokines [ 141 ] Kidney RAW264.7 derived exosomes - Dexamethasone In vitro: - In vivo: LPS- or ADR-induced renal inflammation and fibrosis 1. Effectively delivered into inflamed kidney 2.…”
Section: Application Of Macrophage Membrane Biomimetic Nanoparticlesmentioning
confidence: 99%
“…Owing to the inflammatory homing effects, the macrophage membrane assisted RMN NPs in inflammatory colonic tissues to suppress inflammation. Based on the overproduction of ROS and upregulation of transmembrane glycoprotein CD98 in UC, Ma et al developed a macrophage membrane to coat a pH-responsive MOF carrier loaded with carbon nanodots and CD98 CRISPR/Cas9 plasmid (CCZM) [ 141 ]. The results of cellular uptake in RAW264.7 cells showed that macrophage membrane-coated nanoparticles had a 2.5-fold higher fluorescence intensity than nanoparticles without membrane decoration.…”
Section: Application Of Macrophage Membrane Biomimetic Nanoparticlesmentioning
confidence: 99%